Involvement of immune responses in the eradication of IL-1 alpha gene-transduced tumour cells: mechanisms of tumour rejection and immunotherapeutical implications - Apte, R N; Douvdevani, A; Zoller, M; White, R M; Dvorkin, T; Shimoni, N; Huleihel, M; Fima, E; Hacham, M; Voronov, E (Folia biologica, 1994)
We detected a strong correlation between the constitutive expression of IL-1 alpha and reduced tumorigenicity, using fibrosarcomas which produce the cytokine spontaneously (as an aberration of the transformation process) or upon gene transfer. In fibroblasts intracellular or membrane-associated IL-1 alpha is expressed, whereas the secreted form of the cytokine (IL-1 beta) is absent. Studies on the mechanisms of tumour regression of the IL-1 alpha producing fibroblastoid cell lines indicated that IL-1 alpha potentiates the development of tumour cell-specific CTLs, which are of importance for tumour eradication. It also appears that IL-1 alpha-induced enhanced helper T-cell activity provides auxiliary signals for the growth/development of CTLs. In addition, we observed a massive lymphocytic infiltrate in IL-1 alpha producing regressing tumours which ultimately replaces the tumour's mass. Non-adaptive effector cells, activated locally by IL-1 alpha expressing fibrosarcoma cells, were also shown to contribute, to some extent, to the eradication of IL-1 alpha expressing fibrosarcomas. Local IL-1 alpha expression potentiated antigen presentation, by the malignant fibroblasts as well as by tissue-resident antigen-presenting cells, and by this anti-tumour immune responses were further potentiated. Mice, in which IL-1 alpha producing tumours regressed, developed systemic immunity and rejected a challenge with a non IL-1 producing violent tumour cell line. It appears that endogenous IL-1 alpha, being a strong inducer of cytokine production, operates a whole cytokine cascade (such as IL-6, CSFs and prostaglandins). However, studies using clonal populations have indicated that IL-1 alpha is essential for fibrosarcoma eradication, whereas the other cytokines possibly amplify and sustain its action. We assume that most naturally occurring tumours are not constitutive IL-1 alpha producers, as it would be disadvantageous for the tumour to express a cytokine which increases its immunogenicity. However, IL-1 non-producing fibrosarcomas can be induced easily to express IL-1 transiently, by treatment with cytokines/LPS, and upon the induction of the cytokine they shift from progressor to regressor tumours. We also obtained positive immunotherapeutical effects when treating mice bearing IL-1 non-producing fibrosarcomas with cells from the same line induced in vitro to express IL-1 alpha. The results may shed light on a novel parameter affecting tumour-host interactions, namely cytokine expression by the tumorous cells, and may provide the basis for new immunotherapy protocols for fibrosarcoma management.
Keywords: rejekce štěpu; T-lymfocyty pomocné-indukující; transfekce; interleukin-1; Interleukin-1; Lymphocytes, Tumor-Infiltrating; tumor infiltrující lymfocyty; Mice; buňky 3T3; cytotoxické T-lymfocyty; Fibrosarcoma; 3T3 Cells; Mice, Nude; Gene Expression; imunoterapie; zvířata; Graft Rejection; myši nahé; fibrosarkom; Transfection; myši; Immunotherapy; nádorová transformace buněk; exprese genu; T-Lymphocytes, Cytotoxic; T-Lymphocytes, Helper-Inducer; Cell Transformation, Neoplastic; Animals